Aplikasi Penjadwalan Belajar Mengajar Pada Bimbingan Belajar Dengan Menggunakan Metode Waterfall - Rachmat Hidayat; Asep Sayfulloh (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2021)
The internet has been widely used in various fields, such as information, telecommunications, trade, to education, making it easier for a company or institution to provide information that is very useful for the community. tutoring education. Researchers conducted a case study at tutoring sites in Tangerang City, including ELC English tutoring, Rizki General Bimbel, Al-Hikmah Religious Education, with a large number of students and teachers, still applying the conventional scheduling system, where the admin will contact students and teachers by telephone if there are teaching classes, other obstacles the admin forgets to notify students and teachers if there is a schedule, the schedule given is not appropriate and clashes with other classes, students or teachers cannot contact the admin to get schedule information. By utilizing information technology, these problems can be facilitated by making a web-based scheduling application developed using the waterfall method. This development method includes needs analysis, design, implementation, and testing. In the needs analysis stage, business process modeling is carried out based on the results of interviews with stakeholders and problem analysis. The results of the application design produce applications that can perform scheduler management of teacher data, lesson data and student data, which will be stored in the database.